Infection dynamics of a V. splendidus strain pathogenic to Mytilus edulis: In vivo and in vitro interactions with hemocytes. Issue 70 (November 2017) - Ben Cheikh, Yosra; Travers, Marie-Agnès; Le Foll, Frank
Abstract: The pathogenic strain V. splendidus 10/068 1T1 has previously been reported for its virulence to the blue mussel and for its capacity to alter immune responses. In this study, we expanded the knowledge on hemocyte-pathogen interactions by using in vitro and in vivo assays. V. splendidus 10/068 1T1 severely inhibited cell adhesion and acidic vacuole formation unlike the innocuous phylogenetically related V. splendidus 12/056 M24T1 which had no effect on these cell functions. Furthermore, the virulent bacteria decreased hemocyte viability (59% of viability after 24 h). Infection dynamics were explored by using a model based on water tank cohabitation with septic mussels infected by GFP-tagged V. splendidus 10/068 1T1. Experimental infections were successfully produced (16.6% and 45% mortalities in 3 days and 6 days). The amount of GFP Vibrio in seawater decreased during the experiment suggesting its horizontal transfer from diseased animals to healthy ones. At the same time periods, bacteria were detected in hemocytes and in various organs and caused necrosis especially in gills. Total hemocyte count and viability were affected. Taken together, our results indicate that the pathogen V. splendidus 10/068 1T1 colonizes its host both by bypassing external defense barriers and impairing hemocyte defense activities. Highlights: Establishment of mussel experimental infection by V. splendidus via cohabitation. Detection of the GFP- V. splendidus strain in mussel tissues and hemocytes. Necrosis of gills during experimental infection by the virulent Vibrio strain. The virulent strain alter phagolysosome maturation, hemocyte adhesion and viability.